The Identity Target in the Post-2015 Development Agenda : Enabling Access to Services for All - Dahan, Mariana; Gelb, Alan (2016)
Robust personal identification (ID) systems are critical to the success of many development programs. Regardless of the methods used, official ID for all - together with the legal, political, and economic rights it confers - is becoming a priority for governments around the world. Legal ID is on the post-2015 sustainable development goals (SDGs) agenda as SDG target 16.9, urging states to ensure that all have free or low-cost access to widely accepted, and robust identity credentials. The international community should join forces to achieve this goal, as attaining it will also be a key enabler of many other SDGs.